2023
DOI: 10.1101/2023.02.08.527686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia-inducible factor (HIF) activation promotes osteogenic transition of valve interstitial cells and accelerates heart valve calcification in chronic kidney disease (CKD)

Abstract: Objective: Valve calcification (VC) is a widespread complication in chronic kidney disease (CKD) patients on hemodialysis. VC is an active process with the involvement of in situ osteogenic transition of valve interstitial cells (VICs). VC is accompanied by the activation of hypoxia inducible factor (HIF) pathway, but the role of HIF activation in the calcification process remains undiscovered. Approach and Results: Using in vitro and in vivo approaches we addressed the role of HIF activation in osteogenic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…A previous study showed that HG induces HIF‐1α stabilisation in LECs (Han et al, 2015) and because HIF pathway activation was shown to be associated with the promotion of vascular and valve calcification (Balogh et al, 2019; Csiki et al, 2023; Mokas et al, 2016), we next investigated whether this mechanism is involved in the HG‐induced promotion of calcification in HuLECs. To address this, we treated HuLECs with OM (2.5 mmol/L Pi, 0.3 mmol/L Ca, 48 h) under NG and HG conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that HG induces HIF‐1α stabilisation in LECs (Han et al, 2015) and because HIF pathway activation was shown to be associated with the promotion of vascular and valve calcification (Balogh et al, 2019; Csiki et al, 2023; Mokas et al, 2016), we next investigated whether this mechanism is involved in the HG‐induced promotion of calcification in HuLECs. To address this, we treated HuLECs with OM (2.5 mmol/L Pi, 0.3 mmol/L Ca, 48 h) under NG and HG conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It is increasingly clear that hypoxia and HIF‐1 activation are involved in the osteogenic phenotype switch and calcification of VSMCs and VICs (Balogh et al, 2019; Csiki et al, 2023; Mokas et al, 2016; Tóth et al, 2022). In accordance with that here, we showed that calcification of HuLECs is attenuated in the absence of HIF‐1α or HIF‐2α, suggesting that hyperglycaemia‐induced stabilisation of HIF‐1α and HIF‐2α and subsequent activation of the HIF‐1 pathway plays a critical role in HG‐induced promotion of calcification (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia promotes the macrophages' disposition to the kidney, which produces profibrotic cytokines (as a transforming growth factor) and activates renal fibroblasts by inducing pro-inflammatory adhesion molecules and chemokines [99,262]. Hypoxia also directly activates fibroblasts to increase extracellular matrix deposition due to increasing collagen and tissue-metalloproteinase-I production inhibitors while diminishing collagenase expression [101,263]. The activated fibroblasts, inflammatory cell enrollment, and injury to tubule epithelial cells contribute to tubulointerstitial fibrosis development.…”
Section: Recurrent Aki Episodesmentioning
confidence: 99%